Chemoembolization outcomes for hepatocellular carcinoma in cirrhotic patients with compromised liver function. Issue 7 (20th November 2013) - Dorn, David P.; Bryant, Mary K.; Zarzour, Jessica; Smith, J. Kevin; Redden, David T.; Saddekni, Souheil; Aal, Ahmed Kamel Abdel; Gray, Stephen; White, Jared; Eckhoff, Devin E.; DuBay, Derek A.
Abstract Background Transarterial chemoembolization (TACE) is recommended as a treatment for unresectable hepatocellular carcinoma (HCC) in patients with normal underlying liver function. The efficacy of TACE in cirrhotic patients with compromised liver function is unknown. Methods All 'first' TACE interventions for HCC performed at a single institution from 2008 to 2012 were retrospectively reviewed (n = 190). Liver function was quantified via the Child's score. Tumour necrosis after TACE was quantified via the mRECIST criteria. Results The 'first' TACE procedures of 100 Child's A and 90 Child's B/C cirrhotic patients were evaluated. As expected, the lab‐model for end‐stage liver disease (MELD) score was significantly higher in the Child's B/C group. Although the number of tumours were similar between the groups, both the size of the largest tumour and the total tumour diameter were greater in the Child's A group. There were no significant differences in post‐TACE tumour necrosis between groups. The median survival after TACE was significantly longer in the Child's A compared with Child's B/C patients (21.9 versus 13.7 months, P = 0.03). Conclusions TACE appears to be equally efficacious in cirrhotic patients regardless of their Child's classification based upon equivalent mRECIST measures of tumour necrosis. However, inferior survival after TACE was observed in the Child's B/C group.